2017
DOI: 10.1080/07399332.2017.1367002
|View full text |Cite
|
Sign up to set email alerts
|

U.S. mothers' behaviors and preferences when choosing physicians for their families: Assisting “Chief Medical Officers”

Abstract: We performed an online study of 320 U.S. mothers to determine how this group, generally regarded as the "Chief Medical Officers" of their families, find physicians for their families. We also aimed to uncover mothers' information preferences with the goal of helping health care systems improve the content they offer. Mothers responded how they chose their last family medicine physician, and the level of importance they placed on various types of provider information when making that decision. Mothers rated pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
2
1
Order By: Relevance
“…In a rare circumstance, the present study found that men perceived higher "doctor's appearance" rating score as compared to women when choosing a paediatric general practice and this association was statistically significant. This finding was also contrary to a previous study that indicate mothers rated personality characteristics of health care provider to be an important element when deciding on a provider in comparison to fathers (Perrault & Inderstrodt-Stephens, 2017). Parents with lower-income level perceived higher "doctor's appearance" rating score as compared to parents with higherincome level when choosing a paediatric general practice and this association was statistically significant.…”
Section: Role Of Family Characteristics While Choosing a Paediatric General Practicecontrasting
confidence: 99%
“…In a rare circumstance, the present study found that men perceived higher "doctor's appearance" rating score as compared to women when choosing a paediatric general practice and this association was statistically significant. This finding was also contrary to a previous study that indicate mothers rated personality characteristics of health care provider to be an important element when deciding on a provider in comparison to fathers (Perrault & Inderstrodt-Stephens, 2017). Parents with lower-income level perceived higher "doctor's appearance" rating score as compared to parents with higherincome level when choosing a paediatric general practice and this association was statistically significant.…”
Section: Role Of Family Characteristics While Choosing a Paediatric General Practicecontrasting
confidence: 99%
“…11,14 Survey studies, such as that by Bornstein et al, 15 found that professional factors and management practices outweigh a doctor's personal characteristics, while another study by Kenny et al 12 indicated care quality as the most essential, where a summation scale broadly grouped together technical care, interpersonal care and continuity. Perrault and Inderstrodt-Stephens 13 found communication style as being most important, but in the absence of including any elements of technical quality. Discrete choice experiments have indicated that, for many, technical quality outweighs interpersonal skills, and yet a substantial proportion of respondents placed the highest value on interpersonal skills.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of consumer preferences in choosing a doctor present a variety of results, dependent in part on what the study design can measure and what doctor characteristics are included. [8][9][10][11][12][13] Studies exploiting administrative data to determine revealed preferences have pointed to consumers choosing primary care doctors who resemble themselves in terms of observable characteristics, namely, age and gender. 11,14 Survey studies, such as that by Bornstein et al, 15 found that professional factors and management practices outweigh a doctor's personal characteristics, while another study by Kenny et al 12 indicated care quality as the most essential, where a summation scale broadly grouped together technical care, interpersonal care and continuity.…”
Section: Introductionmentioning
confidence: 99%